Is Colombia Ready for "Bilingualism"? ¿Colombia está lista para el "bilingüismo"? - Gabriel Vicente Obando Guerrero; Ana Clara Sánchez Solarte (Universidad Nacional de Colombia, 2008)
Currently, the Colombian government is attempting to implement programs such as "Colombia Bilingüe". The effectiveness of this type of project depends on a number of factors, some of which do not have to do with policies or standardization, but with academic requirements and issues that might be neglected while focusing on the outcome rather than on the process of expecting foreign language learners to become proficient in a second or foreign language (L2). This paper examines the academic needs that have to be met in order to achieve government goals in a fair and rewarding way for teachers, students and stakeholders. Also, the way similar foreign language policies have been implemented in other countries is briefly described. En la actualidad el gobierno colombiano está tratando de implementar el programa "Colombia Bilingüe". El éxito de este tipo de iniciativas depende de varios factores, algunos de los cuales no están relacionados con políticas o con estándares, sino con factores y requisitos académicos que pueden estar siendo dejados a un lado. Este artículo trata sobre las necesidades académicas que deben resolverse para lograr las metas propuestas por el gobierno, pero de forma que el proceso sea justo y gratificante para estudiantes, profesores y directivas. Así mismo se aborda brevemente la forma como políticas sobre el aprendizaje de lenguas extranjeras se han puesto en marcha en otros países.